Institutionalisation of convergent medical innovation: an empirical study of the MRI-guided linear accelerator in the Netherlands and the United States - Hehakaya, Charisma; Moors, Ellen H.M. (Taylor and Francis Ltd., 2025)
Although convergence is a major trend in the development of medical innovations, the implications of the institutionalisation of convergent innovation are understudied. This paper explores how the institutionalisation of convergent innovation affects the organisation of health care, by using operational domains and categories of the Non-adoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) and the Institutional Readiness (IR) approach respectively. We use an illustrative comparative case study on the institutionalisation of MRI-guided linear accelerator (MR-Linac) technology in the Netherlands and the United States. Empirically, we conducted 66 interviews with different professionals in the health care system around MR-Linac. The findings show that institutionalisation of convergent innovation affects the organisation of health care by: changing the traditional organisation of solving a medical problem, thereby transforming and reorganising work in the health care environment, providing opportunities for individual user development, collective action and cross-sectoral developments, and requiring the additional work of evaluating convergent innovation, including administrative tasks, innovation and research activities within and across institutions. The insights offered are also relevant for understanding convergence in the medical field, and for rethinking medical innovation in general.
Keywords: complex innovation; convergence; convergent innovation; convergent technology; Institutionalisation; organisational design; Management of Technology and Innovation